The finance and accountancy desktop guide : for the non-financial manager - Tiffin, Ralph (London : Thorogood, 1998)
A guide to all aspects of accounting and financial and business literacy, split into two sections: the first covers the main areas and explains terms and techniques; and the second goes into greater depth. The text includes coverage of cash flow forcasting and appraising capital expenditure.
oif 11/03/15
Loan
Keywords: Accounting; Finance